2012
DOI: 10.1016/j.conbuildmat.2012.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial transition zones in recycled aggregate concrete with different mixing approaches

Abstract: h i g h l i g h t s " Nanoindentation was applied to characterize nanomechanical properties of ITZs. " SEM was implemented to analyze the microstructures of ITZs. " Two-stage mixing approach is proved to improve the properties of the new ITZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(97 citation statements)
references
References 30 publications
(35 reference statements)
5
89
0
3
Order By: Relevance
“…The uniformity of the elastic modulus and hardness across aggregate-paste in PCC is also dependent on the sample locations since calcium hydroxide crystals may exist in the porous regions between aggregates and cement paste. Many studies define the existence and dimension of ITZ in cementitious mixtures as the distance between the aggregate and paste where the values of the elastic modulus and hardness are instable and there is a great variation in the values between studies [11,13,38]. However, identifying the ITZ and determining the dimension by just defining the instable area from the nanomechanical test results may not be an accurate way due to the possible mismatching between mechanical properties and actual phases that are usually highly heterogeneous.…”
Section: Nanomechanical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniformity of the elastic modulus and hardness across aggregate-paste in PCC is also dependent on the sample locations since calcium hydroxide crystals may exist in the porous regions between aggregates and cement paste. Many studies define the existence and dimension of ITZ in cementitious mixtures as the distance between the aggregate and paste where the values of the elastic modulus and hardness are instable and there is a great variation in the values between studies [11,13,38]. However, identifying the ITZ and determining the dimension by just defining the instable area from the nanomechanical test results may not be an accurate way due to the possible mismatching between mechanical properties and actual phases that are usually highly heterogeneous.…”
Section: Nanomechanical Characterizationmentioning
confidence: 99%
“…The higher porosity of the ITZ can significantly reduce the mechanical properties and durability of cementitious mixtures by allowing easier penetration of aggressive species into the mixtures [9]. Recently, nanoindentation which is a useful tool to derive the local nanomechanical properties of the materials, has been widely used to directly characterize the nanomechanical properties of the interphase region [10][11][12][13][14][15][16]. Although there are a lot of studies which have investigated the microstructure and mechanical properties of interphase region in PCC, studies on investigating chemical properties and integrating with mechanical and microstructural features of this region are limited.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be kept in mind that it is just a model interfacial system that allows producing a bond between matrix and aggregate. In fact, the material preparation (mixing) greatly affects the formation of ITZ in concrete [14][15][16][17][18][19][20][21][22][23][24][25][26]. Pope and Jennings [26] reported that the interfacial zone of a limestone mortar is reduced in size by controlling the water-aggregate contact through a pre-coating procedure or by mixing the cement paste separately.…”
Section: Introductionmentioning
confidence: 99%
“…However, its mechanical properties are not widely known because direct mechanical characterization methods are difficult to perform. The nano-indentation technique, which is potentially the only one able to directly evaluate the mechanical properties of the interface, has its limitations due the great variability of the measurements [14,15]. That is why different authors have thus tried to perform tests with simplified models such as sandwiched specimens in which cement paste (or mortar) is in contact with coarse aggregate [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…For successful recycling, several variables should be considered in the design of new concrete mixtures: the percentage of recycled material, the percentage of recycled coarse ore, the percentage of fine material, the water/cement relation, the density of recycled material, the use of thinners, shrinkage (workability), mechanical resistance, and homogeneity (Chang et al, 2011). The microstructure study of recycled concrete presents new challenges as the interfacial zone (ITZ) has two zones difficult to identify according to the age/hydration (Kong et al, 2010;Li et al, 2012): old and modern rapid-setting concrete, with different compositions, porosities, densities, age, resistivity, hydration and hardness. The reduction method for the size of the hardened hydraulic concrete in order to obtain gravel could result in loss by pulverization, aggregate sizes ≤ ¼ of an inch (6.4 mm), porous areas with their corresponding forms, sizes and distribution in the pores of the matrixes, which increase the superficial area increasing the demand of CP in the new mixture (Koeu et al, 2011;Gómez-Soberon, 2012).…”
Section: Introductionmentioning
confidence: 99%